2012
DOI: 10.1177/0899764012440180
|View full text |Cite
|
Sign up to set email alerts
|

Do Contexts Matter for Willingness to Donate to Natural Disaster Relief? An Application of the Factorial Survey

Abstract: Research on charitable giving mostly investigates the effects of various donor characteristics on willingness to donate. Analyzing intentions of charitable giving to natural disaster relief, the first aim of this article is to show how situational characteristics of the recipientsthat is, country contexts and disaster specificities-matter. Theoretical propositions for the effects of recipient contexts and donor attributes are derived from basic mechanisms of prosocial behavior that appear recurrently in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Charitable giving research traditionally focuses on reasons for donating (Andorfer & Otte, 2013;Bennett, 2003), although we have recently witnessed increasing outputs focusing specifically on how donors select charities to support (Chapman et al, 2018;Feeny et al, 2019;Neumayr & Handy, 2019;van Dijk et al, 2019). It has been suggested that donors do not necessarily deliberate extensively when selecting charities but base their choices on heuristic cues such as the credibility of charity patrons or friendships with fundraisers (Breeze, 2013).…”
Section: Charitable Choice and Differences In Donation Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…Charitable giving research traditionally focuses on reasons for donating (Andorfer & Otte, 2013;Bennett, 2003), although we have recently witnessed increasing outputs focusing specifically on how donors select charities to support (Chapman et al, 2018;Feeny et al, 2019;Neumayr & Handy, 2019;van Dijk et al, 2019). It has been suggested that donors do not necessarily deliberate extensively when selecting charities but base their choices on heuristic cues such as the credibility of charity patrons or friendships with fundraisers (Breeze, 2013).…”
Section: Charitable Choice and Differences In Donation Preferencementioning
confidence: 99%
“…4. To identify potential donor segments who may be predisposed to types of charities defined by charitable and political attitudes, thereby addressing an area of charitable marketing which has received limited consideration (Andorfer & Otte, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the literature has identified that donors’ willingness to give is conditional on contextual factors. Andorfer and Otte () find that donors are more likely to give the highest level of contributions in two situations: (1) when there is a devastating disaster, such as the Southeast Asian tsunami in 2004 or the Haiti earthquake in 2010, and (2) when they perceive that charitable organizations can effectively allocate their donations to these victims. Saxton, Neely, and Guo () find that American donors’ willingness to give is positively related to the organization's level of financial and performance disclosure.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Much is known about the broader determinants of charitable giving (best reconciled by Bekkers and Wiepking 2011a). However, such research has come at the expense of understanding charitable choice (Andorfer and Otte 2013;Breeze 2013) and in particular what drives international charity donations (Wiepking 2010). Donors do not share their generosity equally (Strombach et al 2014), with data from both Europe and North America demonstrating that donors prioritise domestic over international causes (Casale and Baumann 2015;Micklewright and Schnepf 2009).…”
Section: Introductionmentioning
confidence: 99%